2004
DOI: 10.1074/jbc.m411240200
|View full text |Cite
|
Sign up to set email alerts
|

The N Termini of Friend of GATA (FOG) Proteins Define a Novel Transcriptional Repression Motif and a Superfamily of Transcriptional Repressors

Abstract: Members of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 46 publications
3
67
0
Order By: Relevance
“…In vitro studies have shown that GATA-4 (or the closely related factors GATA-5 and -6) can bind and trans-activate several genes expressed in differentiating and terminally differentiated members of the parietal and zymogenic cell lineages (Tamura et al, 1993;Mushiake et al, 1994;Nishi et al, 1997;Sakamoto et al, 1998Sakamoto et al, , 2000, and studies with chimeric mice underscore the in vivo contributions of GATA-4 to expression of these genes (Jacobsen et al, 2002). In vitro, FOGs can either enhance or repress the activity of GATA-4, depending on the promoter studied (Lu et al, 1999;Viger, 2001, 2003;Lin et al, 2004). Gata4 ki/ki distal gastric epithelium exhibits augmented expression of Shh, suggesting that GATA-4:FOG interaction plays a direct or indirect role in limiting the expression of this factor.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that GATA-4 (or the closely related factors GATA-5 and -6) can bind and trans-activate several genes expressed in differentiating and terminally differentiated members of the parietal and zymogenic cell lineages (Tamura et al, 1993;Mushiake et al, 1994;Nishi et al, 1997;Sakamoto et al, 1998Sakamoto et al, , 2000, and studies with chimeric mice underscore the in vivo contributions of GATA-4 to expression of these genes (Jacobsen et al, 2002). In vitro, FOGs can either enhance or repress the activity of GATA-4, depending on the promoter studied (Lu et al, 1999;Viger, 2001, 2003;Lin et al, 2004). Gata4 ki/ki distal gastric epithelium exhibits augmented expression of Shh, suggesting that GATA-4:FOG interaction plays a direct or indirect role in limiting the expression of this factor.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of this transcriptional network results in a variety of human diseases including congenital heart disease, dilated cardiomyopathy, and cardiac hypertrophy (Frey and Olson, 2003;Olson, 2004;Clark et al, 2006). Central to the regulation of these developmental processes are the cardiac transcription factors GATA4 (Watt et al, 2004), NKX2.5 (Cripps and Olson, 2002), Hand (McFadden et al, 2005), nuclear factors of activated T-cell (NFAT) c3 and c4 (Molkentin, 2000;Graef et al, 2001;Bushdid et al, 2003), Foxp4 and FOG2 (Svensson et al, 2000;Lin et al, 2004), and T-box transcription factors TBX1 and TBX5 (Plageman and Yutzey, 2005), all of which have been shown to regulate cardiomyocyte proliferation, cardiacspecific gene expression, and proper patterning of the developing heart.…”
Section: Introductionmentioning
confidence: 99%
“…Both FOG-1 and FOG-2 have been shown to interact with CtBP-2, but the functional significance of this interaction is unclear, as disruption or deletion of this site in vitro or in vivo does not affect FOG function [9,16,21]. We have previously identified a second domain of FOG proteins localized at the N-terminus of all vertebrate FOG proteins, the FOG repression motif, which is necessary for transcriptional repression [22]. Mutations within this motif abrogate the ability of FOG-1 or FOG-2 to repress GATA-mediated transactivation of target promoters.…”
Section: Introductionmentioning
confidence: 99%